Penerapan Pencatatan Keuangan Digital Dalam Kinerja UMKM di Pasar Gedangan - Sherly Aulia Yunianti; Mochammad Ilyas Junjunan (Accounting Journal of Ibrahimy (AJI), 2026)
This study aims to examine the influence of digital financial record-keeping on the performance of MSMEs in Pasar Gedangan. By adopting a qualitative method, data were collected through interviews and observations of ten MSME actors who have used digital recording systems. The results indicate that the implementation of digital financial record-keeping enables MSMEs to manage their finances more effectively and improve business outcomes. However, several challenges were identified, such as a lack of understanding of technology and limited access to necessary devices. This study recommends the implementation of training and assistance programs to help MSMEs optimize the use of this technology.